IOP4, the Interactive Optical Photo-Polarimetric Python Pipeline - Pedrosa, Juan Escudero; Agudo, Ivan; Morcuende, Daniel; Otero-Santos, Jorge; Bonnoli, Giacomo; Piirola, Vilppu; Husillos, Cesar; Bernardos, Mabel; Lopez-Coto, Ruben; Sota, Alfredo; Casanova, Victor; Aceituno, Fran J.; et al. (IOP Publishing Ltd, 2025)
IOP4 is a pipeline to perform photometry and polarimetry analysis of optical data from Calar Alto (CAHA) and Sierra Nevada (OSN) observatories. IOP4 implements Object Relational Mapping to seamlessly integrate all information about the reduction and results in a database that can be used to query and plot results, flag data, and inspect the reduction process in an integrated fashion with the whole pipeline. It also ships with an already built-in web interface that can be used out of the box to browse the database and supervise all pipeline processes. It is built to ease debugging and inspection of data. Reduction from five different instruments are already implemented: RoperT90, AndorT90, DIPOL (at OSN 0.9 m telescope), AndorT150 (OSN 1.5 m telescope), and CAFOS (CAHA 2.2 m telescope). IOP4's modular design allows for easy integration of new observatories and instruments, and its results have already featured in several high-impact refereed publications. In this paper we describe the implementation and characteristics of IOP4.